1991
DOI: 10.2169/internalmedicine1962.30.458
|View full text |Cite
|
Sign up to set email alerts
|

Post Transplanted Infective Endocarditis.

Abstract: The patient, a 51-year-old man, was receiving immunosuppresants for 2 yr after renal allotransplantation. He had heart failure with aortic regurgitation, fever, anemia and a history of odontectomy on admission. He wasresistant to medical treatments and died from cerebral emboli. Onautopsy, vegetation of the aortic valve was identified. Progression of atherosclerosis, which may have been due to steroids and chronic rejection, was prominent. This report is the first case of infective endocarditis following organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…In contrast, in the immunosuppressed kidney transplant patients, the distribution of pathogens seems to be much wider, and also includes uncommon opportunistic infections as well as common, community‐acquired ones. In additional, fungal endocarditis was over‐represented in the cases described above, diagnosed in 16% of cases compared to only 2% of IE cases in the general population . The prognosis seems to be worse in fungal rather than in bacterial IE, which is expressed in higher need of heart surgery during the acute infection (7/12 patients, 60%), and higher mortality rate (7/12, 60%).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…In contrast, in the immunosuppressed kidney transplant patients, the distribution of pathogens seems to be much wider, and also includes uncommon opportunistic infections as well as common, community‐acquired ones. In additional, fungal endocarditis was over‐represented in the cases described above, diagnosed in 16% of cases compared to only 2% of IE cases in the general population . The prognosis seems to be worse in fungal rather than in bacterial IE, which is expressed in higher need of heart surgery during the acute infection (7/12 patients, 60%), and higher mortality rate (7/12, 60%).…”
Section: Discussionmentioning
confidence: 92%
“…In 10 (14%) of the cases, the pathogen was isolated from a vegetation specimen taken either during heart surgery or autopsy. The stratification of the isolated pathogens is shown in Table …”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In a review of 14 reported cases of endocarditis, bacterial endocarditis occurred in 11 patients (78.5%), and fungal endocarditis was found in three cases (21%). Three cases were caused by S. aureus , two by Candida albicans , two by Corynebacterium species, and one each by Aspergillus species, Clostridium ramosum , Streptococcus viridans , Nocardia asteroides , vancomycin‐resistant enterococci, Erysipelothrix rhusiopathiae , and Brucella melitensis (4, 7–16). Klebsiella pneumoniae and Streptococcus bovis endocarditis in renal transplant recipients have also been reported (17, 18).…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, there has been no homograft transplantation in liver-transplanted patients. In a review of the literature we could not find an exact percentage of incidence of heart valve operations in pre-or post-transplant patients; we did, however, find that there is a higher incidence of marantic endocarditis [4] and bacterial endocarditis [6] in post-transplant patients. Complications of "nonhomograft" valves jeopardize transplanted patients because of a higher thromboembolic complication rate and a fives times higher risk of prosthetic valve endocarditis in the first 9 postoperative months [l].…”
mentioning
confidence: 86%